18F-FDG PET molecular imaging: A relevant tool to investigate chronic inflammatory rheumatisms in clinical practice? - Pean De Ponfilly – Sotier, Marie; Seror, Raphaële; Nocturne, Gaetane; Besson, Florent L. (Frontiers in Medicine, 2022)
18F-Labeled Fluorodeoxyglucose-Positron Emission Tomography (18F-FDG PET) is a molecular imaging tool commonly used in practice for the assessment of many cancers. Thanks to its properties, its use has been progressively extended to numerous inflammatory conditions, including chronic inflammatory rheumatism (CIR) such as rheumatoid arthritis (RA), spondylarthritis (SpAs) and polymyalgia rheumatica (PMR). 18F-FDG PET is currently not recommended for the diagnostic of CIRs. However, this whole-body imaging tool has emerged in clinical practice, providing a general overview of systemic involvement occurring in CIRs. Numerous studies have highlighted the capacity of 18F-FDG PET to detect articular and extra articular involvements in RA and PMR. However, the lack of specificity of 18F-FDG limits its use for diagnosis purpose. Finally, the key question is the definition of the best way to integrate this whole-body imaging tool in the patient’s management workflow.